Study on outcome of gastrocnemius recession surgery in diabetic equinus contracture - Gill, Narinder Singh (2014)

(untitled)
BACKGROUND: Diabetic equinus secondary to gastrocnemius contracture is a known predominant risk factor in diabetic foot ulceration characterized by reduction of ankle dorsiflexion. Recession surgery involves release of the gastrocnemius muscle at its aponeurosis and is one of the treatments of choice in improvement of diabetic equinus contracture. OBJECTIVE: To measure degree of improvement of ankle dorsiflexion and length gained at gastrocnemius aponeurosis following gastrocnemius recession surgery in diabetic equinus contracture. To assess correlation between the lengths gained at gastrocnemius aponeurosis with degrees of improvement in ankle dorsiflexion following surgery. METHODOLOGY: Total of 76 patients was recruited in the Orthopaedic clinics and wards at Penang General Hospital. Presence of gastrocnemius equinus was established with a positive Silfverskiold test. Gastrocnemius recession surgery using the Modified Strayer Technique was done following failed conservative therapy. Pre and post-operative ankle dorsiflexion was measured. Length gained at gastrocnemius aponeurosis was measured at 6 weeks post-operative using Ultrasound done in maximal ankle dorsiflexion. Results were analyzed using SPSS version 20.0 RESULTS: The severity of equinus contracture did not correlate to chronicity of diabetes mellitus. There was improvement of ankle dorsiflexion seen at 6 weeks post-operatively. It ranged from 6 to 16 degrees and was coupled with statistical significant length gained at gastrocnemius aponeurosis that ranged from a mean of 0.8cm to 3.8cm. Mean improvement ofankle dorsiflexion was 11.05 degrees. Mean improvement of length gain at gastrocnemius aponeurosis was 1.54cm. CONCLUSION: Gastrocnemius recession surgery appropriately addresses diabetic equinus secondary to gastrocnemius contractures by improving ankle dorsiflexion and is evidenced by a significant increase in length at the aponeurosis.